2017
DOI: 10.5430/jnep.v7n9p78
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ professional values on patient care provisions and decisions

Abstract: Objective: To determine the relationship of professional value system of nurses to their duties and functions specifically on patient care provisions and decisions among selected government hospitals in Hail city, Kingdom of Saudi Arabia. Methods: The study utilized a Descriptive Correlational method of research inquiry where a 26-item questionnaire on nurse professional value system (NPVSR) were distributed to 150 staff nurses employed in 3 government hospitals in the City of Hail after which, their responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…These results are consistent with those reported by Kubsch et al [30]. However, Al Shammari et al indicated that no relationship was found between age and professional values [23]. It can be said that time and experience are factors that facilitate movement throughout the transformation continuum; older nurses have more experience that reinforce their professional values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with those reported by Kubsch et al [30]. However, Al Shammari et al indicated that no relationship was found between age and professional values [23]. It can be said that time and experience are factors that facilitate movement throughout the transformation continuum; older nurses have more experience that reinforce their professional values.…”
Section: Discussionsupporting
confidence: 90%
“…All the mentioned factors can influence the nurses' perceptions of professional values. Moreover, it can be said that values are innate and flexible; they might change over time depending upon the everyday events that affect thought and behavior [23].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding current position, there are (50.4%) of them work as a nurse, and the majority (81.5%) of them have from 1 -< 6 years with mean experience 5.6 ± 6. Figure (8) presents that total score level of staff nurses regarding levels of Maslach's burnout inventory; there are (62.90%) of staff nurses have a high level; and (37.10%) have moderate score level. (2) there are negative associations between emotional exhaustion of the nurse's staff with the subscales of professional values which are (privacy, competence, improve standards, Conditions of employment, and collaborate) with p-values (0.0001, 0.022, 0.0001, 0.001, and 0.001 respectively).…”
Section: Table (1)mentioning
confidence: 99%
“…The application of professional values by nurses in their practice is associated with better quality of patient care. They have a positive impact on nurses' judgment and choices in their care for patients, and their decisions and actions, with compliance to standards (Al Shammari et al, 2017;Stainton and Hughson 2017). Professional values also help nurses to identify resolutions for ethical problems when making decisions (Donmez Ozsoy, 2016).…”
Section: Introductionmentioning
confidence: 99%